(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
This paper describes an important multimedia online project, dedicated to a number of different sources concerning Late Medieval and Early Renaissance music. The project, created by the University of Vienna, is continuously fostered by scholars all over Europe. DOI 10.17464/9788867742783